Determination of SOX9 Gene Expression In Brain Tumours Among East Coast Malaysia Population - NB, Md Dzali; WR, Wan Taib; MN, Zahary; NH, Abu Bakar; AZ, Abd Latif; F, Ahmad; H, Jaafar (IIUM Medical Journal Malaysia, 2019)
Introduction: SOX9, a members of SOX family, plays a significant roles in developmental processes during embryogenesis, including brain tissue. Few studies have shown that SOX9 has been involved in tumourigenesis of several types of cancer including brain tumour. However, such studies are still lacking in the Malaysian population. The aim of this study was to determine SOX9 expression level in several types of brain tumours in East Coast Malaysia. Materials and Methods: Five formalin-fixed pariffin-embedded brain tumour samples of Malay descendants were sectioned by using microtome. RNA extraction was performed with slight modification by adding Trizol during tissue lysis. The RNA was converted to cDNA using reverse transcription technique before SOX9 expression was detected using RT q-PCR assay in brain tumours normalized to non-neoplastic brain tissues. Results: Overall results displayed that SOX9 gene in all samples were up-regulated. SOX9 overexpression was found in both high and low grade glioma (anaplastic and pilocytic astrocytoma respectively). This is consistence with both low grade (benign) and atypical meningioma. Secondary brain tumour also showed up-regulation when compared to normal brain tissue. Conclusion: Up-regulation in SOX9 expression in selected brain tumours in Malay patients revealed its significant roles in brain tumourigenesis. Functional studies should be carried out to observe the SOX9 functions and mechanism whether they should reflect their diverse roles in Malaysia population.